Impact of Constraints and Behavioral Motivations on Loyalty of Horse Racing Spectators - Rahimi Hoseini, Seied Vali; Amani, Maryam (Journal of History Culture and Art Research, 2018)
The present study aims to investigate the effect of constraints and behavioral motivations of spectators on their loyalty in horse racing competitions in Golestan province. The research method is descriptive and analytical. The statistical population includes spectators of the horse racing in three cities of Aqqala, Bandar Torkaman and Gonbad-e Kavus, which includes a sample size of 388 people. The data gathering tool is the standard questionnaire for sport spectators’ behavior (Yu, 2010) including 80 items measuring 5 general factors of internal motivators, internal constraints, external motivators, external constraints, and loyalty. SPSS 21 and Amos 18 software are used to analyze the data. The result of the test shows that the internal motivators and constraints of spectators and the external motivators and constraints of their behavior affect their loyalty with a path coefficient of .78, -.38, .75, and -.42, respectively. Given that the support of the special horse and rider is the internal motive of the spectators, more spectators can be encouraged to participate in horse race competition by inviting the country's top horseback riders and even the best riders in Asia and their horses to the horse riding competitions of Golestan province.